Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.7759/cureus.7005
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis Patients in Saudi Arabia: Prevalence of Depression and its Extent of Severity

Abstract: BackgroundMultiple sclerosis (MS) is a serious chronic autoimmune disorder of the central nervous system of unknown etiology. MS-related depression is a common mood disorder recognized within the medical community. However, their association is ambiguous, underdiagnosed, undertreated and less reported. ObjectivesThe study aimed to estimate the point prevalence and severity of depression among multiple sclerosis patients in Saudi Arabia. Materials and methodsWe conducted an observational cross-sectional study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 26 publications
3
19
1
Order By: Relevance
“…In the current study, the prevalence of depression and anxiety differed among different age groups, with the older age groups showing higher levels of both mild anxiety and depression, on average. This finding is not consistent with the results of the previous study [ 19 ]. Our study also found a significant relationship between depression and the health state of MS patients, with depression correlating with a deteriorating health status.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the current study, the prevalence of depression and anxiety differed among different age groups, with the older age groups showing higher levels of both mild anxiety and depression, on average. This finding is not consistent with the results of the previous study [ 19 ]. Our study also found a significant relationship between depression and the health state of MS patients, with depression correlating with a deteriorating health status.…”
Section: Discussioncontrasting
confidence: 99%
“…The association between MS and psychiatric disorders such as depression and anxiety is a complex relationship that has not yet been fully understood [ 19 ]. MS is a chronic disease associated with a considerable effect on the patient’s quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ultiple Sclerosis (MS) is an inflammatory, chronic, and autoimmune disease, i.e., associated with the destruction of the myelin sheath in the central nervous system (Patten 2020). MS development is attributed to a combination of genetic and environmental factors (Alhussain et al 2020). The epidemiology of MS has changed in recent decades; numerous reports are released every day on the increasing prevalence of the disease worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies attempted to address the correlation between MS and depression [ 10 ]. In Saudi Arabia, there is limited current literature about the incidence and relationship between depression and MS [ 18 - 19 ]. In a meta-analysis conducted by Etemadifar et al, there is limited availability of data with varied quality scores, diagnostic criteria, sample size, and methods [ 20 ].…”
Section: Introductionmentioning
confidence: 99%